Sustainable tourism and heritage: Enhacing and plannig tools - Mayor Salvi, Marta (UPV[Scientia], 2017)
The book "Sustainable Tourism and Heritage. Tools for Planning and Management" has been edited by Universitat Politècnica de València and encouraged by the Ministry of Agriculture and Fisheries, Food and Environment of Spain. It is based on the need to manage tourism from a heritage conservation and protection perspective, from the recognition of the importance of heritage as a driver for local development, and from the necessity to create responsible tourist products that are respectful of their natural, cultural and social environment. This handbook includes fourteen worksheets on various aspects of tourism enhancement and planning: natural resources, built heritage, movable and intangible heritage, landscape, climate, facilities, tourism service providers, tourism demand, participatory processes, heritage interpretation, recreational activities and tourism product design, recreational carrying capacity, and tourism communication. The worksheets are available in printed version but also in digital version that can be downloaded from http://bit.ly/2057_Fichas. Thus, each user can create its own files and update them as appropriate